Does annealing improve the interlayer adhesion and structural integrity of FFF 3D printed PEEK lumbar spinal cages?. (February 2020) - Basgul, Cemile; Yu, Tony; MacDonald, Daniel W.; Siskey, Ryan; Marcolongo, Michele; Kurtz, Steven M.
Abstract: Polyaryletheretherketone (PEEK) has been commonly used for interbody fusion devices because of its biocompatibility, radiolucency, durability, and strength. Although the technology of PEEK Additive Manufacturing (AM) is rapidly developing, post-processing techniques of 3D printed PEEK remain poorly understood. AM of PEEK has been challenging because of its high melt temperature (over 340 °C) and requires specialized equipment which was not commercially available until recently. A lumbar fusion cage design, used in ASTM interlaboratory studies, was 3D printed with a medical grade PEEK filament via Fused Filament Fabrication (FFF) under two different print speeds. PEEK cages were then annealed above the PEEK's glass transition temperature, at 200 °C or 300 °C. AM cages were CT scanned to determine the porosity before and after annealing. Mechanical tests were conducted on cages according to ASTM F2077 (ASTM F2077, 2014). SEM images helped to evaluate the cages' surface morphology before and after heat treatment. It was observed that annealing did not produce markedly better mechanical properties at either temperature, however, it had an effect on the cages' mechanical properties at lower printing speed under all loading conditions. Although the structure of the pores changed after annealing, annealing conditions examined here as a post-processing method were not able to decrease the undesired porosity formed during the 3D printing process or change the failure mechanism, which is due interlayer debonding. Graphical abstract: Image 1 Highlights: Annealing did not produce markedly better mechanical properties at either temperature. Annealing was not able to decrease the porosity formed during the 3D printing process. Annealing at higher temperature affected the surface morphology of FFF PEEK cages.